Dietary and lifestyle factors associated with troublesome gastroesophageal reflux symptoms in Vietnamese adults - Quach, Duc Trong; Luu, Mai Ngoc; Nguyen, Phong Van; Vo, Uyen Pham-Phuong; Vo, Cong Hong-Minh (Frontiers in Nutrition, 2023)
Background Dietary and lifestyle habits related to troublesome gastroesophageal reflux symptoms (tGERS) differ significantly across populations. There have yet to be studies on the Vietnamese population. Aims To identify dietary and lifestyle habits associated with tGERS in Vietnamese adults. Methods A cross-sectional survey was conducted among Vietnamese adults aged 18 years and older from March 2023 to May 2023. Participants were recruited online through a widely read national newspaper and Facebook, one of Vietnam’s most popular social media platforms. The survey questionnaire comprised 27 questions covering participants’ basic demographic information, dietary and lifestyle habits, the presence and characteristics of tGERS, and inquiries about specific dietary and lifestyle patterns, foods, and beverages associated with tGERS. Results A total of 4,400 valid responses were collected, including 2050 participants without tGERS and 2,350 participants with tGERS. Multivariate analysis showed several factors associated with tGERS, including eating beyond fullness (OR 1.383, CI95% 1.127–1.698), tight clothing (OR 1.627, CI95% 1.256–2.107), stress (OR 1.566, CI95% 1.363–1.800), and insomnia (OR 1.321, CI95% 1.129–1.546). Among habits associated with tGERS, eating beyond fullness was the most frequently reported (64.6%). Interestingly, although a short meal-to-bed time and staying up late after midnight were not risk factors for tGERS, they were two common factors associated with tGERS in symptomatic participants, particularly those with nocturnal reflux symptoms. For food triggers, the three most common ones were greasy foods (71.9%), sour/spicy soups (64.7%), and citrus fruits (36.0%). In terms of beverages, carbonated soft drinks were at the top of triggering tGERS (40.3%), and beer and orange juice were the second and third most common triggers, accounting for 35.7 and 30.6%, respectively. Conclusion We reported the dietary and lifestyle habits associated with tGERS in Vietnamese adults for the first time. These findings will serve as a basis for future studies on the primary prevention and nondrug management of tGERS in Vietnam.